Blastic plasmacytoid dendritic cell neoplasm: the first report of two cases treated by 5‐Azacytidine. (1st April 2014) - Laribi, Kamel; Denizon, Nathalie; Ghnaya, Habib; Atlassi, Mustapha; Besançon, Anne; Pineau‐Vincent, Fabienne; Gaulard, Philippe; Petrella, Tony
Abstract Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare hematologic malignancy which was first included as an independent cutaneous lymphoma in the 2008 World Health Organisation (WHO) classification (1). BPDCN usually has an extremely poor prognosis, with quick relapses after chemotherapy (2; 3). Here, we report two cases of patients diagnosed in 2011 with BPDCN and myelodysplasia, and who were treated for the first time with 5‐azacytidine (5‐Aza); a drug approved by the Food and Drug Administration (FDA) and mainly used in the treatment of myelodysplastic syndrome (Kaminskas E, et al. 2005 Clin Cancer Res, 11, 3604–8). The first case was an 81‐year‐old man who presented with unusual CD10+, CD56‐ immunohistochemistry and 45X, ‐Y abnormality using fluorescent in situ hybridization (FISH) analysis. The second case was a 78‐year‐old woman who manifested monosomy 13 and chromosome instability due to D13S319 locus deletion in 13q14 as determined by FISH. Both patients showed excellent responses of their skin lesions after one cycle of chemotherapy, and their hematological disease was stabilized; however, pulmonary sepsis set in, followed by neutropenia after the fourth and the fifth cycle of treatment, that is, eight and 9 months postdiagnosis, respectively, leading to patient death.